There is No "Axillary Tail": Rethinking the Assumption of James Spence. Issue 2 (9th February 2022) - Teplica, David; Cooney, Emmett; Jeffers, Eileen; Sayers, Michael
Abstract : Summary: Widely quoted, "the axillary tail of Spence" refers to a contiguous extension of adipose angling superolaterally from the primary breast into the axilla. Described anecdotally in 1871, the "tail of Spence" has been considered important to the fields of general surgery, oncology, plastic surgery, and anatomy ever since. Despite the ubiquitous presence of the concept in literature, clinical discussions, and educational settings, we argue against the very existence of Spence's "tail." While pinch-testing and topographically mapping 316 consecutive patients in preparation for breast and gynecomastia surgery, we found a consistent pattern of focal fat mounds without continuity between breast and axilla. The absence of an uninterrupted superolateral tail was reaffirmed while analyzing 20 research participants who were pinch-tested with calipers and topographically mapped, specifically to define fat pad anatomy. We documented that the axillary breast mound was always distinct from the primary breast and that all women and many men had an additional "lateral chest wall tail" that never angled toward the axilla. In most, rolling the shoulder girdle anteriorly created a visible groove between the axillary mound and the primary breast, with little or no pinchable fat beneath that crease. With all deference to Spence, we have established that the outer half of the chest is consistently defined by three focal adipose structures—an axillary mound, the primary breast mound, and a previously unnamed "lateral chest wall tail"—with no anatomic evidence of an "axillary tail" of fat extending superolaterally from breast to axilla.